Neurochemical and behavioural impact of C18 fatty acids in male mice postweaning. (June 2013) - Yamamuro, Yutaka; Yamaguchi, Yuki; Abe, Shin; Takenaga, Fumio
Dietary components, particularly essential fatty acids, affect the expression and maintenance of normal physiological phenotypes. However, the influence of C18 fatty acids that are abundantly present in the normal diet is unclear. We focused on the behavioural and neurochemical effects of C18 fatty acids during postweaning development in male mice. An AIN-93G diet supplemented with 8% stearic acid (C18:0), 3% oleic acid (C18:1), 3% linoleic acid (C18:2) or 3% α-linolenic acid (C18:3) was provided from four weeks of age for eight weeks. At 12 weeks of age, novel exploratory behaviour and social interaction tests were carried out. One week after the last behavioural test, the brain of each mouse was removed. The frequency of social interactive behaviour was decreased by approximately 70% in the C18:0 group compared to the basal diet group, but there was no difference in cumulative time. The frequency of social interaction showed a positive correlation to cumulative time in mice fed with the experimental diets except for C18:0. Dietary C18 fatty acids following weaning had no impact on brain fatty acid composition except for the C18:3 diet. Furthermore, the neurochemical properties to be especially noted were that choline acetyltransferase activity was absolutely higher in C18:0 diet-fed mice than in the other groups, especially in the frontal cortex where it was 1.7-fold higher than in the basal diet-fed group. The present results reveal a significant possibility of neurochemical and behavioural effects of dietary fatty acids, and saturated fatty acids are of special importance during the postweaning period.